Extraversion and neuroticism as predictors of salivary cortisol levels in public speaking - Gloria García de la Banda (Análisis y Modificación de Conducta, 2025)
This study investigated the role of extraversion and neuroticism on the salivary cortisol responses of 45 students participating in a required public speakin presentation.